2008
DOI: 10.1175/2007jcli1348.1
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization Effects on Observed Surface Air Temperature Trends in North China

Abstract: A dataset of 282 meteorological stations including all of the ordinary and national basic/reference surface stations of north China is used to analyze the urbanization effect on surface air temperature trends. These stations are classified into rural, small city, medium city, large city, and metropolis based on the updated information of total population and specific station locations. The significance of urban warming effects on regional average temperature trends is estimated using monthly mean temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

35
335
2
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(379 citation statements)
references
References 27 publications
35
335
2
7
Order By: Relevance
“…Locally, however, the effects may be larger, and much recent work has emphasized China (e.g., Ren et al, 2008) because here the effect may be larger than in other parts of the world . Urban growth has been dramatic in the recent 30 years across eastern China, but an important consideration is that very few of the series are located in rural locations [see discussion in recent papers by Li et al (2014) and Zhao et al (2014)].…”
Section: Urbanization Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Locally, however, the effects may be larger, and much recent work has emphasized China (e.g., Ren et al, 2008) because here the effect may be larger than in other parts of the world . Urban growth has been dramatic in the recent 30 years across eastern China, but an important consideration is that very few of the series are located in rural locations [see discussion in recent papers by Li et al (2014) and Zhao et al (2014)].…”
Section: Urbanization Effectsmentioning
confidence: 94%
“…Averages produced for China or parts of China, e.g., by Li et al (2014) and Zhao et al (2014), use networks of different station densities, including both rural and urban stations. Others (e.g., Ren et al, 2008) omit the more urban stations. For both types, averaging doesn't consider land use except at the stations.…”
Section: Urbanization Effectsmentioning
confidence: 99%
“…The key of this method depends on whether or not those sites or stations can be objectively classified. In general, such a classification utilizes either population data [6][7][8][9][10][11][12][13][14][15][16][17] or satellite data (such as nighttime light imagery and land cover dataset) [18][19][20][21][22][23] as well as the geographic location of the stations. In addition, Empirical Orthogonal Function (EOF) [24,25], Principal Component Analysis (PCA) [26,27] and station metadata [28] can also be applied to define reference or rural stations.…”
mentioning
confidence: 99%
“…Some previous studies indicated that urbanization has little impact on regional warming [7,13,26,27]. However, recent investigations have suggested that the urbanization process can not only increase the local daily temperature, but also play an essential role in regional climate change [6,9,12,[14][15][16][17][20][21][22][23][24][28][29][30]35,36]. Using the OMR method, Zhou et al [29] and Zhang et al [30] found that the urbanization exerts a significant influence on temperature trends in eastern China.…”
mentioning
confidence: 99%
See 1 more Smart Citation